Situation Report: Romania, 24 April 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu's Tour of Asia and the Middle East: Jordan and Tunisia Economic Co-operation with Developing Countries Active Participation in Work of UN Disarmament Committee Italian and Romanian Military Delegations Exchange Visits Romania Buys British Airlines Economic Relations with Libya Relations with the USA Writers Union Council Formally Elects New Chairman and Bureau Members Supply, Services, and Workers Cafeterias